The impact of biological inputs on drought stress resistance in Celtis caucasica L. seedlings - Amin Heidarpour Monfared; Mohammad Reza Pourmajidian; Farhad Rejali; Mohammad Hojati; Parvin Ramak (علوم محیطی)
Introduction: Unfavorable environmental conditions result in stress in plants and so disrupt their growth and survival. Today, soil microorganisms, especially fungi and growth-promoting bacteria, involved in various biological processes in plant growth and soil nutrient cycling, are suggested to reduce the effects of environmental stress. Materials and methods: In order to investigate the effect of drought stress and biological inputs on vegetative characteristics of Celtis caucasica (diameter and height growth, root length, fresh and dry weight of root and shoot, and seedling colonization), a factorial experiment (Mycorrhizal factors in two levels of inoculation with arbuscular mycorrhizal fungi and without inoculation (control), bacteria in four levels of Pseudomonas, Azpyrilum, Azotobacter and control treatments, and drought stress at three levels of field capacity (80, 60 and 40%) was performed in a complete randomized block design and four replications in the greenhouse of the Natural Resources Office in Lorestan Province. Results and discussion: The results showed that the highest diameter growth of Celtis caucasica L. seedlings was observed at moderate drought stress in Pseudomonas-fungi and Azotobacter-fungi treatments with an average of 0.554 and 0.525 mm, respectively. The highest height growth was observed at moderate drought stress in Pseudomonas-fungi and Azotobacter-fungi treatments with an average of 21.55 and 20.55 cm, respectively. The highest leaf area was observed at low drought stress in Pseudomonas-fungi and then with Azotobacter-fungi with an average of 116 and 116/75 cm2, respectively. The least of these traits was observed in high drought stress in the control group and azosperyllium treatment. The highest and lowest root length was observed at moderate drought stress in Pseudomonas and Azotobacter treatments, and at low drought stress in the control group and Pseudomonas-fungi treatments, respectively. The highest root fresh weight was observed at moderate drought stress in Azotobacter and Pseudomonas with an average of 16.7916 and 16.7941 g, respectively. The lowest values were obtained at low and moderate drought stress for the control group. The highest and lowest root dry weight was observed at high drought stress in Azotobacter and Pseudomonas treatments, and at low drought stress in control and Azospirillum-fungi treatments, respectively. The highest fresh and dry weight of shoot were obtained at moderate drought stress in Pseudomonas-fungi and Azotobacter-fungi treatments, and the lowest was observed at low drought stress in control and azosperyllium treatments. The highest percentage of colonization was observed in low drought stress in Pseudomonas-fungi and Azotobacter-fungi treatments with an average of 44. 175 and 42.675%, respectively; and the lowest was observed at high drought stress in the control group with 26.42% and azosperyllium treatments, with 26.695%. Conclusion: Microbial and fungal factors and their interactions increase root colonization, plant growth characteristics, and water uptake and thus increase plant tolerance to adverse environmental conditions such as drought stress.